PENGARUH MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) TERHADAP KEMAMPUAN PENALARAN ADAPTIF MATEMATIS SISWA - Nopitasari, Dian (Universitas Wiralodra, 2016)
This  research   was   conducted   in one of junior high school in Tangerang academic  year  2015/2016.  Aimed  to analyze the effect of CPS model on the students? mathematical adaptive reasoning skills. The method used in  this  study  was a quasi   experimental   method with randomized posttest only control group design. Samples were obtained as many as two classes by cluster random sampling technique.  Based  on  result  of  hypothesis this    show    that    students? mathematical adaptive    reasoning      skills    who    were taught  by  creative  problem solving  model was   higher   than   the students?mathematical adaptive reasoning skills of those who were taught by conventional model